A rat's tale - Seidler, Tor.; Marcellino, Fred ([New York, NY] : Farrar Straus Giroux, 2008)
"Montague, an artistic young rat living beneath the streets of New York City, thinks he can do nothing to save his friends from extermination until he achieves a better understanding of both himself and his ne'er-do-well uncle"--Source other than Library of Congress.
Keywords: Rats -- Fiction; Artists -- Fiction; Uncles -- Fiction; Self-perception -- Fiction; Rats -- Juvenile fiction; Artists -- Juvenile fiction; Uncles -- Juvenile fiction; Self-perception -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Juvenile fiction